2017
DOI: 10.1186/s12917-017-1051-2
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of indicators and methods of measurement used to evaluate the impact of dog population management interventions

Abstract: BackgroundDogs are ubiquitous in human society and attempts to manage their populations are common to most countries. Managing dog populations is achieved through a range of interventions to suit the dog population dynamics and dog ownership characteristics of the location, with a number of potential impacts or goals in mind. Impact assessment provides the opportunity for interventions to identify areas of inefficiencies for improvement and build evidence of positive change.MethodsThis scoping review collates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 67 publications
(139 reference statements)
1
39
0
Order By: Relevance
“…Starting in North America during the 1970s, concerns about pet overpopulation and implementing population control measures have historically been at the forefront of desexing advocacy originating from both the veterinary profession and the shelter community, focusing on both animal welfare and public health aspects associated with free-roaming dogs [71][72][73][74][75]. However, considering both the substantial body of literature advocating in favor of desexing as a means of population control and the widespread use of desexing in shelters and by private practice veterinarians over the last 40-50 years [3,13,14,76-79], the body of evidence investigating the effectiveness of desexing to actually achieve population control in companion and shelter dogs is surprisingly slim [80,81], and the evidence from such studies does not generally support the existence of an effect of desexing programs on population control, as discussed below.…”
Section: Population Controlmentioning
confidence: 99%
“…Starting in North America during the 1970s, concerns about pet overpopulation and implementing population control measures have historically been at the forefront of desexing advocacy originating from both the veterinary profession and the shelter community, focusing on both animal welfare and public health aspects associated with free-roaming dogs [71][72][73][74][75]. However, considering both the substantial body of literature advocating in favor of desexing as a means of population control and the widespread use of desexing in shelters and by private practice veterinarians over the last 40-50 years [3,13,14,76-79], the body of evidence investigating the effectiveness of desexing to actually achieve population control in companion and shelter dogs is surprisingly slim [80,81], and the evidence from such studies does not generally support the existence of an effect of desexing programs on population control, as discussed below.…”
Section: Population Controlmentioning
confidence: 99%
“…Our systematic review found that dog population management is conducted in many countries globally [15,16], carried out by different groups (e.g., researchers and animal welfare or government agencies), applying different methods to different populations types (restricted and unrestricted) and using different indicators to monitor the impact of the intervention. It is therefore difficult to synthesise the evidence base and assess the true impact of dog population management techniques [3,16], despite the quantity of work being conducted. Very few of the reviewed studies allowed robust conclusions to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Where free-roaming dogs exist in high densities, they can be considered an issue in terms of public health (e.g., transmission of rabies and other zoonotic pathogens) [5][6][7], the environment (e.g., threatening the survival of wildlife) [8][9][10], and the animals' welfare state [2,[11][12][13]. Population management therefore typically focusses on free-roaming dogs [14] to control the population size and-depending on the approach taken-to improve dog health and welfare and mitigate against public health and environmental problems [15,16].…”
Section: The Dog Populationmentioning
confidence: 99%
See 2 more Smart Citations